Evaluation of consumer attitudes towards purchase intention on women’s skincare products in sri lanka: Special reference to anuradhapura district - Senavirathne, T.N.; Kumaradeepan, V. (University of Jaffna, 2020)
Most women like to keep their appearance in superb condition and they have not enough consideration about the harm and dangerous effects being made to the body and the person. The problem was the basis for the research. This study attempted to gain knowledge about consumer attitudes towards purchase intention on Women’s skincare products in Sri Lanka with special reference to Anuradhapura District. Based on the literature review, the study found out that most of the consumer attitudes were strongly related to purchasing intention procedure. Consumer attitude was related to the factors of Knowledge, Trust, Familiarity, brand image, product quality, and Advertising. This research was exploratory research with a quantitative perspective and the population of the study consisted of above 15 years older women of Anuradhapura District. Data collection has been undertaken as an anonymous survey for a week. Randomly selected the female customers who use beauty products and who attend beauty centers located in Anuradhapura District. A total of 150 questionnaires were distributed to female cosmetic consumers aged between 15-65 years old. Statistical packages for social science (SPSS) 16.0 are used for statistical analysis and the survey is analyzed descriptively using tables, frequencies and percentages. The hypotheses have been tested using Pearson correlation, Regression and multiple regression analysis indicated that Product quality was highly significantly related to consumer purchase intention and ANOVA checked the fitness of the model. The research results showed that there is a positive and significant relationship between factors of Customer attitudes (knowledge, trust, product familiarity, and product quality, advertising and brand image.) towards purchase intention on women’s skincare products in Sri Lanka. The researcher provided further suggestions.
Keywords: Consumer attitude; Purchase intention and skin care products